Urgensi Pembentukan Lembaga Pemerintahan Khusus di Bidang Pengelolaan Peraturan Perundang-Undangan - Herlin Wijayati; Indah Dwi Qurbani; Endrianto Bayu Setiawan; Ricardo Simatupang (Jurnal Hukum IUS QUIA IUSTUM, 2024)
Legislation is a sub-system of national law that functions to actualise the implementation of national and state administration according to the ideals established by the national legal system. However, currently the policy of legislation is facing systemic problems, which are related to the institutional governance of the formation of legislation. In response to this problem, this study presents the following formulation of the problem, namely how to design the reconstruction of the institution that forms the legislation in order to create legal order in Indonesia. This legal research is normative in nature that uses conceptual and statutory approaches. The analysis technique used is descriptive-analytical by conducting a qualitative analysis of legal norms. There are two conclusions drawn. First, the problem of institutional governance occurs because of the large number of government institutions involved in the formation of legislation coupled by the absence of consistency of government institutions in the field of the formation of legislation. The regulation of the authority attribution in the formation of legislation according to Article 8 of Law No. 12 of 2011 has resulted in a large number of legislation, especially regulations of ministers/chiefs of institutions. As the result, the practical problems arising are disharmony and regulatory bulge. Second, as a solution to resolve the issue, the mandate of Article 99A of Law No. 15 of 2019 must be implemented immediately, namely by establishing a non-ministerial government institution that carries out government affairs in the field of forming laws and regulations. Failure to establish such a government institution will have implications for the number of uncontrolled laws and regulations and will further worsen the quality of laws and regulations, both in terms of the formation process and their substance.Keywords: Government Institutions, Institutional Arrangement, Laws AbstrakPeraturan perundang-undangan merupakan subsistem hukum nasional yang difungsikan untuk mewujudkan penyelenggaraan kehidupan berbangsa dan bernegara sesuai cita hukum nasional. Akan tetapi, saat ini kebijakan peraturan perundang-undangan sedang dihadapkan pada permasalahan sistemik, yang terkait dengan tata kelola kelembagaan pembentukan peraturan perundang-undangan. Terhadap permasalahan tersebut, penelitian ini menetapkan rumusan masalah yakni bagaimana desain rekonstruksi kelembagaan pembentuk peraturan perundang-undangan untuk menciptakan tertib hukum di Indonesia. Penelitian hukum ini bertipe normatif dengan menggunakan pendekatan konseptual dan peraturan perundang-undangan. Teknik analisis bertipe deskriptif-analitis dengan cara melakukan analisa norma hukum secara kualitatif. Ada dua kesimpulan yang diperoleh. Pertama, masalah tata kelola kelembagaan terjadi karena banyaknya lembaga pemerintahan yang dilibatkan dalam pembentukan peraturan perundang-undangan serta belum adanya keajekan lembaga pemerintahan di bidang pembentukan peraturan perundang-undangan. Diaturnya kewenangan atribusi dalam pembentukan peraturan perundang-undangan menurut Pasal 8 UU No. 12 Tahun 2011 telah mengakibatkan banyaknya jumlah peraturan perundang-undangan, khususnya peraturan menteri/kepala lembaga. Akibatnya, masalah praktis yang timbul adalah disharmoni dan obesitas regulasi. Kedua, sebagai langkah solutif untuk menyelesaikan persoalan tersebut, maka amanat Pasal 99A UU No. 15 Tahun 2019 harus segera dijalankan, yaitu dengan cara membentuk lembaga pemerintahan non kementerian yang menjalankan urusan pemerintahan di bidang pembentukan peraturan perundang-undangan. Dengan tidak dibentuknya lembaga pemerintahan tersebut akan berimplikasi pada jumlah peraturan perundang-undangan yang tidak terkontrol serta semakin memperburuk kualitas peraturan perundang-undangan, baik dari segi proses pembentukan maupun substansinya.Kata Kunci: Lembaga Pemerintah, Penataan Kelembagaan, Peraturan Perundang-Undangan